[Two steelpan men] - (:unkn) unknown (Guardian Litho, [Trinidad and Tobago], 2011)
The postcard shows two men, each playing the steelpan, the national instrument of Trinidad and Tobago. Also printed on the postcard is a three course menu.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Steel drum (Musical instrument); Musicians; Menus; Local term--Steelpan